Amyloid‐β plaques may be reduced in advanced stages of cerebral amyloid angiopathy in the elderly. Issue 5 (17th June 2020) - Okamoto, Koichi; Amari, Masakuni; Fukuda, Toshio; Suzuki, Keiji; Takatama, Masamitsu
Abstract : We examined 29 cases in which cerebral amyloid angiopathy (CAA) was detected among routine aged autopsies. Most cases with severe CAA had many amyloid‐β (Aβ) plaques in the occipital cortex. Nonetheless, two cases had few Aβ plaques with many small vessels and capillaries with CAA. In the two cases, severe CAA was widely distributed, except in the frontal lobes. Aβ deposits in capillaries often showed the characteristic pattern of dysphoric amyloid angiopathy. A few naked plaques were present. Although Aβ plaques were sparse near small vessels with CAA, there were many Aβ plaques distant from small vessels with CAA. Some of the remaining plaques had a moth‐eaten appearance. Based on Aβ‐positive star‐like appearance and results of double immunohistochemistry for glial fibrillary acidic protein and Aβ1–42, some astrocytes appeared to contain Aβ. Ionized calcium‐binding adapter molecule 1 (Iba1)‐positive microglia were scattered within the neuropil, with some present around small vessels with CAA. Iba1‐positive microglia also seemed to phagocytose Aβ in several senile plaques by double immunostaining. Neurons and neurites identified with a monoclonal antibody against phosphorylated tau (clone AT8) were occasionally detected in sparse plaque areas, with AT8‐identified dot‐like structures present around capillaries with CAA. Accumulation of T lymphocytes was detected around vessels in the subarachnoid space in one case. The morphological changes detected in our two cases were similar to those of morphological markers of plaque clearance after Aβ immunotherapy. Nonetheless, our cases did not receive Aβ immunotherapy, but similar pathologies were observed. Overall, advanced CAA cases, including our two cases, may be examples of plaque clearance without Aβ immunotherapy. Further studies are needed to resolve the mechanism of Aβ plaque clearance using these cases.